2015
DOI: 10.1093/aobpla/plv043
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of invading alien plant species on water flows at stand and catchment scales

Abstract: The impacts of invasions by alien plant species on the quantity of rainwater that reaches rivers and streams have been studied in several countries. Some studies have found that there is a large impact and others have found little or no impact. These conflicting conclusions can be explained largely by differences in the structure (e.g. height, depth of root systems) and the physiology (e.g. evergreen, deciduous, water stress tolerance) between the alien and the indigenous plant species. The greater the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 147 publications
3
62
0
5
Order By: Relevance
“…In the long term, due to competition, the community will probably be composed of even larger trees at lower densities. We document that changes in the vegetation have been followed by hydrological changes, as previously observed in other regions [8,13,18].…”
Section: (A) Woody Encroachmentsupporting
confidence: 77%
See 1 more Smart Citation
“…In the long term, due to competition, the community will probably be composed of even larger trees at lower densities. We document that changes in the vegetation have been followed by hydrological changes, as previously observed in other regions [8,13,18].…”
Section: (A) Woody Encroachmentsupporting
confidence: 77%
“…This 'missing' rain is substantial given that the potential evapotranspiration in the region is estimated at 77% of annual rainfall [52] and only the excess water will recharge groundwater reserves and provide streamflow. Classical studies on forest management have demonstrated the strong relationship between tree biomass and hydrological processes [16], and an increase in tree biomass in periodically dry ecosystems has been reported to cause remarkable decrease in streamflow [8,13,16,18]. Rain interception by the canopies, therefore, has the potential to exert a strong influence on the ground water recharge and streamflow at the scale of a watershed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NIAPS included fewer taxa than Versfeld et al (1998), the taxa comprise contrasting growth forms. They also vary in their physiology, phenology, rooting depths, leaf areas and leaf area indexes, and other factors that affect their potential water-use (Calder, 1999;Görgens and Van Wilgen, 2004;Lavorel and Garnier, 2002;Lavorel et al, 1997;Le Maitre, 2004;Le Maitre et al 2015). A key trait that is directly related to interception, transpiration and plant growth is the leaf-area index (Calder, 1999;Running and Coughlan, 1987;Zhang et al, 1999).…”
Section: Refining the Water-use Modelmentioning
confidence: 99%
“…A key trait that is directly related to interception, transpiration and plant growth is the leaf-area index (Calder, 1999;Running and Coughlan, 1987;Zhang et al, 1999). The limited data on the leaf-area index of the invading taxa mapped for the NIAPS suggest that it explains some of the observed variations in water-use between different taxa (Le Maitre et al, 2015). Interception losses are often considered important (Calder, 1999).…”
Section: Refining the Water-use Modelmentioning
confidence: 99%
See 1 more Smart Citation